Analisa Metode Perceptron Prediksi Penyediaan Buku Perpustakaan Sesuai Kebutuhan Mahasiswa (Studi Kasus di Universitas Islam Negeri Sumatera Utara Medan) - Ahmad Taufik Al Afkari Siahaan (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2018)
As a public organization, libraries are required to provide services according the expectations ofthe users, which can provide real-time information, timely and easily accessible in accordance with theneeds of the users of library services including students. The need for a library book that fits the needs ofstudents is important in order to help the learning process better and can help broaden students. WithPerceptron algorithm is one way to predict what books are much needed student. The data relating to theprovision of library books analyzed and categorized. Next will be processed using Artificial Neural Networkswhich will provide an output that supplies information about the library books that fit the needs of studentsin the future.